Nuevo documento sobre la inscripción celtibérica del “Cerro de Bámbola” (Calatayud, Zaragoza) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Presentation of a new document about the Celtiberian  inscription  from Cerro de  Bámbola (Calatayud, Zaragoza).